Analysis of the neutron and proton contributions to the pygmy dipole mode in doubly magic nuclei - Yuksel, E.; Khan, E.; Bozkurt, K. (ELSEVIER, 2012)
The electric dipole excitations are investigated in the framework of the self-consistent HF + RPA approximation with Skyrme interactions. Magic O, Ca, Ni and Sn isotopes are used to investigate low-lying modes. Neutron and proton transition densities analysis of each nucleus is provided to examine the behavior of Pygmy Dipole Resonance (PDR) of nuclei under excitation, showing a complex pattern along the nuclear chart. The PDR in the very neutron-rich Ca-70 nucleus exhibits a novel mode of excitation, the so-called arch mode. The collectivity of the PDR is also analysed. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Giant resonances; Pygmy dipole mode; RPA; GIANT-RESONANCES; CROSS-SECTIONS; STRENGTH; STATES; QUADRUPOLE; EXCITATION; SKIN; Physics